Kecelakaan Akibat Kondisi Jalan dalam Perspektif Yuridis - Ayudyanti, Ika; Wasis, Wasis (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
The purpose of this study was to analyze accidents due to road conditions based on the perspective of the Civil Code and Law Number 22 of 2009 and analyze the government's responsibility for accidents due to road conditions. This study used a normative juridical method, a statutory approach, a historical approach, and a case approach. The data sources were obtained from primary and secondary legal materials, which were analyzed using deductive logic techniques. Based on the Civil Code and Law Number 22 of 2009, accidents due to road conditions were unlawful acts committed by the government. The government's responsibility for accidents due to road conditions was not only carried out by repairing damaged roads but must be responsible to victims by providing compensation either materially or immaterially. The government did not enforce its obligation to repair damaged roads, resulting in a traffic law incident.